Sistemática de análise de falhas de equipamento agrícola sob a ótica de projeto de produto - Franceschi, Alessandro de (2015)
Swine industry in Brazil, due to its growth in recent years, has generated a great quantity of waste, especially in the liquid form, which can be used, by means of agricultural equipment employment, in soil treatment and correction. The majority of small and medium businesses in the Brazilian industrial field of agricultural machinery adopts the trial and error system, not making use of any procedure that systematically assist the process of product design, which can cause problems in the conception generation and/or failure in the operating machinery. The present thesis questions whether the realization of field tests is sufficient to reduce fault problems in the final conception of agricultural machines. Thus, we proposed as main objective a comparative study of failure analysis of a liquid swine waste distributing and incorporating equipment (DLS), realized under two different approaches, by means of prototypes I and II. The first one involves an analysis of equipment testing and experimenting reports (dynamic approach) concerning prototypes I, and II, realized during the usage phase. The second one involves the employment of a systematics of equipment failure analysis - prototype II under the perspective of product design, by applying the FMEA - Failure Modes and Effects Analysis (static approach). In both approaches, the ways results were obtained were specifically analyzed, suggesting improving actions according to certain failure modes. The dynamic approach has aimed the verification of operational activities of the equipment in field, in real work conditions, allowing the identification of faults and problems by means of observation. a partial analysis of equipment failure with a reduced number of considerations if compared to Case II, presenting results that contemplate non-conformities, difficulties, and problems in some subsystems and equipment components during the equipment utilization. The static approach, departing from the equipment functional and structural analysis, allowed evidence in the systems, subsystems, and components on the modes, causes and effects of possible faults, totaling 108 possible modes of failure, whose 11 were considered as potentials. The use of FMEA technique justifies the importance of incorporating a way for preventing faults during every phase and stage concerning the product designing. Therefore, this study verifies that both approaches allow the establishment of a interaction of results, recommendations and suggestions which permit eliminating or minimizing failure in the final conception of agricultural machinery. However, the FMEA technique application within a systematization of fault analysis since the beginning of the equipment design allows for the suggestion of improvement actions in the prototype before it is submitted to tests and experiments.